Academic performance and musculoskeletal pain in adolescents with uncorrected vision problems - Hanne-Mari Schiøtz Thorud; Prabeen Raj Mudvari; Helle K. Falkenberg (BMC, 2024)
Abstract Background Undetected vision problems are common in school children, and a prevalence of up to 40% has previously been reported. Uncorrected vision and lack of optimal eye wear can have a significant impact on almost all aspects of everyday life, such as development and learning, academic performance, pain and discomfort, and quality of life. This study aimed to analyze the relationship between uncorrected vision problems, educational outcomes, and musculoskeletal pain symptoms. Methods A total of 152 school children (15.1 ± 0.8 years, mean ± SD; 40% males) were included in the study. All participants were recruited from a free-of-charge school vision testing program in Kathmandu, Nepal. Academic grades were collected from the school records of the participants' nationwide final grade examinations. A questionnaire was used to record the use of digital devices, screen time, and associated symptoms, including musculoskeletal pain (Wong-Baker FACES Pain Rating Scales). Results A total of 61 children (40%) had uncorrected vision, with a cycloplegic refraction of SER − 0.53 ± 0.52 (mean ± SD). Children with uncorrected vision had significantly more third division grades (26 vs. 9%, p = 0.004) and shoulder pain in general/during screen use (66 vs. 43/40%, p = 0.008/0.003; 2.1/1.9 vs. 1.1/1.0 mean pain score, p = 0.002/0.001) compared with children with normal vision. Sex based subanalyses showed that only girls with uncorrected vision had more third division grades (25 vs. 4%, p = 0.006), and only boys with uncorrected vision had more shoulder pain in general/during screen use (76 vs. 28/31%, p < 0.001; 2.2/2.4 vs. 0.7 mean pain score, p < 0.001), compared with children with normal vision. Conclusions The results of this study showed that even small refractive errors may impact educational outcomes and musculoskeletal pain in adolescents. Most of the participating children had low myopia, easily corrected with glasses. This suggests that regular eye examinations are important in school children, and there is a need for raised awareness among parents, and school- and healthcare personnel.